DEVELOPMENT OF INTELLIGENT CONTROLLER FOR TRAFFIC LIGHTS WITH DYNAMIC PHASE ARRANGEMENT FOR SINGLE-ISOLATED INTERSECTIONS - KAMAL ABBAS , MA YTHEM AL-ADILI (2014)
Traffic congestion has been recognized as a major problem in the modem urban cities as the number of vehicles is increasing and the urbanization, which led to waste the driver's time and accordingly frustration. In order to solve this problem, an integrated system has been developed for managing a single intersection's traffic lights with high stability at all levels of demand. It has circumvented most of the problems those usually pop up when using image processing, obsolete technologies, or wrong control algorithms. V ANET technology with appropriate control algorithm was used to collect road status data and deliver them to the intersection's traffic light controller to make efficient, accurate, and dynamic decisions about traffic light phase planning. The first decision made by the controlling algorithm was the sequence priority. This algorithm expands the Djikestra's shortest path algorithm to choose the optimal dual-green-phase to be operated at a moment of time.